Mechanical behavior of anterior fixed partial dentures made of different materials subjected to static and dynamic loads (2017)
ABSTRACT: The purpose of this study was to assess the mechanical behavior of lithium disilicate, alumina, and zirconia-based ceramic restorations, as well as metal-ceramic restorations, under static and dynamic load, in an upper anterior fixed site. Methods: four models of fixed partial dentures (FPD) were designed, representing alumina, zirconia, and metal-ceramic two-layered systems and a lithium disilicate monolithic system, with a 9 mm2 connector. The variables included were elastic modulus, Poisson’s ratio, and ultimate tensile strength. A static load of 100 N was applied up to 800 N, as well as a dynamic load of 100 and 200 N, calculating von Mises stress and maximum and minimum principal stresses. Results: all models showed a greater concentration of stress under static and dynamic load on the connector region, without exceeding the maximum tensile stress of metal and ceramic structures. The two-layered models showed greater stress concentration on the veneering ceramic compared with the structure. Conclusions: all stresses concentrated on the connector region, producing failure risk at this point of the structures. The veneering ceramic has a greater probability of failure in all two-layered models. The disilicate model can be considered as an alternative for clinical use. The metal-ceramic dentures showed the best distribution on the connector compared to all other models, confirming that they are the gold standard. Keywords: dental prostheses, crowns, ceramics, finite element analysis.